Treatment of children with chemical burns of esophagus with various etiology - A. E. Stryukovsky; V. A. Tarakanov; V. M. Starchenko; N. V. Pilipenko; V. M. Nadgeriev; A. Yu. Gritsenko; E. A. Polyansky; S. A. Sidorenko (Инновационная медицина Кубани)
Background. At present continuous growth of pathology after chemical burns of the esophagus (CBE) in children is observed. The lack of uniform statistical information about this pathology in domestic and foreign literature considerably complicates studying of that nosology. The purpose of the present study is optimization of treatment techniques in children with chemical burns of the esophagus with various etiology and generalization of our own experience of treatment in this contingent of patients.Material and methods. We have analyzed treatment techniques in 147 children with CBE with various etiology and severity for last decade. The general method of diagnosis was esophagogastroscopy performed within the first day of hospitalization. Endoscopic examination showed following stages of CBE: I stage in 36 patients, II stage in 67 cases and 44 patients had III stage.Results. In children with I stage CBE erosive inflammatory process was controlled by conservative therapy in 10–14 days. This cohort of patients from 3–4 day of disease was considered outpatient. Patients with II stage CBE erosive inflammatory changes were treated by complex therapy on 21–23 day. There were surgical complications observed.    Patients with III stage CBE referred in most severe condition. Length of conservative treatment for erosive  inflammatory process was 1 month. In this group of patients we observed complications in 24 cases (16.3%) and bougienage was performed according to different techniques. Duration of bougienage varied from 3 to 24 months. Later on all children were observed out-patiently according to the place of residence.Conclusions. Performed therapy should be complex and differentiated regarding the severity of trauma. Complex treatment technique designed in our hospital is quite efficient and could be recommended for clinical application. All children suffered from CBE are to be followed up refularly. Preventive medical check-up should include endoscopic examination, once every three months to avoid possible esophageal stenosis development. Preventive treatment for esophagitis is mandatory during the period of preventive medical check-up.